Development of a framework for an RFID-based manufacturing process automation system. (11th June 2009) - Lee, W.B.; Cheung, C.F.; Kwok, S.K.; Chan, Y.L.; Chan, K.C.C.; Leung, H.K.N.
The use of radio frequency identification (RFID) in manufacturing process automation is becoming increasingly popular in various industries. However, the integration of RFID with various manufacturing systems is still a challenge. This paper presents the development of a framework for an RFID-based manufacturing process automation system (MPAS) for use in manufacturing industries. The MPAS is characterised by its ability to capture and harness real-time production and process data of semi-finished products and components during the manufacturing and assembly processes. It supports rapid logistics decision-making for the re-allocation of production resources and rectification of bottleneck problems to meet tight delivery schedules. A prototype system has been built and the potential benefit of the system has been realised through a series of implementations in selected reference sites.